Metatranscriptomic profiling reveals diverse tick‐borne bacteria, protozoans and viruses in ticks and wildlife from Australia. Issue 5 (16th May 2022) - Gofton, Alexander W.; Blasdell, Kim R.; Taylor, Casey; Banks, Peter B.; Michie, Michelle; Roy‐Dufresne, Emilie; Poldy, Jacqueline; Wang, Jian; Dunn, Michael; Tachedjian, Mary; Smith, Ina
Abstract: Tick‐borne zoonoses are emerging globally due to changes in climate and land use. While the zoonotic threats associated with ticks are well studied elsewhere, in Australia, the diversity of potentially zoonotic agents carried by ticks and their significance to human and animal health is not sufficiently understood. To this end, we used untargeted metatranscriptomics to audit the prokaryotic, eukaryotic and viral biomes of questing ticks and wildlife blood samples from two urban and rural sites in New South Wales, Australia. Ixodes holocyclus and Haemaphysalis bancrofti were the main tick species collected, and blood samples from Rattus rattus, Rattus fuscipes, Perameles nasuta and Trichosurus vulpecula were also collected and screened for tick‐borne microorganisms using metatranscriptomics followed by conventional targeted PCR to identify important microbial taxa to the species level. Our analyses identified 32 unique tick‐borne taxa, including 10 novel putative species. Overall, a wide range of tick‐borne microorganisms were found in questing ticks including haemoprotozoa such as Babesia, Theileria, Hepatozoon and Trypanosoma spp., bacteria such as Borrelia, Rickettsia, Ehrlichia, Neoehrlichia and Anaplasma spp., and numerous viral taxa including Reoviridiae (including two coltiviruses ) and a novel Flaviviridae ‐like jingmenvirus . Of note, a novel hard tick‐borne relapsing fever Borrelia sp. was identified in questing H. bancrofti ticks which is closely related to, but distinct from, cervid‐associated Borrelia spp. found throughout Asia. Notably, all tick‐borne microorganisms were phylogenetically unique compared to their relatives found outside Australia, and no foreign tick‐borne human pathogens such as Borrelia burgdorferi s.l . or Babesia microti were found. This work adds to the growing literature demonstrating that Australian ticks harbour a unique and endemic microbial fauna, including potentially zoonotic agents which should be further studied to determine their relative risk to human and animal health.